A multi-factor model of panic disorder: Results of a preliminary study integrating the role of perfectionism, stress, physiological anxiety and anxiety sensitivity - Wood, Cristina Mae; Cano-Vindel, Antonio; Salguero, José Martín (Anales de Psicología / Annals of Psychology, 2015)
Background: Panic disorder (PD) is a highly prevalent and disabling mental health problem associated with different factors including perfectionism, stress, physiological anxiety, and anxiety sensitivity regarding physical concerns; however, no studies have analyzed the joint relationship between these factors and PD in a multi-factor model using structural equation modeling. Method: A cross-sectional study was carried out to collect data on these factors and self-reported DSM-IV past-year PD symptoms in a large sample of the general population (N=936). Results: Perceived stress had a significant effect in increasing physiological anxiety, which in turn had an important association with physical concerns. Perfectionism and perceived stress had an indirect relation with past year PD via the mediator role of physiological anxiety and physical concerns. Physical concerns, on one hand, seemed to mediate the impact between perfectionism and PD and, on the other, partially mediated the role between physiological anxiety and PD. Conclusions: Although there is considerable evidence on the association between each of these factors and PD, this model can be considered a broader and productive framework of research on the nature and treatment of PD.